God, action, and embodiment - Tracy, Thomas F., 1948- (Grand Rapids, Mich. : : Eerdmans, 1984)
Revision of thesis (Ph. D.)--Yale University, 1980.
Includes bibliographical references and index.
Keywords: God (Christianity); Psychology, Religious; Philosophical theology; Mind and body; Analogy (Religion)